2006
DOI: 10.3354/ame043033
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bacterioplankton activity after the ‘Prestige’ oil spill off Galicia, NW Spain

Abstract: The response of coastal bacterioplankton communities to the 'Prestige' oil spill in November 2002 was investigated off A Coruña (NW Spain). Abundance and activity (leucine uptake) of bacterioplankton communities were analysed in relation to total soluble hydrocarbon concentrations (THC) measured monthly for 1 yr after the spill. Temperature, chlorophyll a, total and particulate organic carbon (TOC and POC, respectively), along with oxygen concentrations were also measured. The highest THC values (140 µg l -1 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The polar membrane lipid analyses were conducted from samples filtered at sea and would have included both freeliving microbes and microbes adsorbed to oil flocs. If biomass estimates from polar membrane lipids provide a more faithful indication of microbial abundance than flow cytometry, then our observations of consistent microbial standing stocks inside and outside of the slicks agree with studies of the 1979 IXTOC I oil spill in the Bay of Campeche (Atlas et al 1980) and the 2002 Prestige oil spill off the coast of Portugal (Bode et al 2006), where there were no differences in pre-and post-spill bacterial abundances. An alternative explanation is that since polar membrane lipids were similar inside and outside the slick, the abundance data are indicating that there was more biomass per cell inside the slick than outside the slick (i.e.…”
Section: Microbial Biomass and Abundancesupporting
confidence: 85%
See 1 more Smart Citation
“…The polar membrane lipid analyses were conducted from samples filtered at sea and would have included both freeliving microbes and microbes adsorbed to oil flocs. If biomass estimates from polar membrane lipids provide a more faithful indication of microbial abundance than flow cytometry, then our observations of consistent microbial standing stocks inside and outside of the slicks agree with studies of the 1979 IXTOC I oil spill in the Bay of Campeche (Atlas et al 1980) and the 2002 Prestige oil spill off the coast of Portugal (Bode et al 2006), where there were no differences in pre-and post-spill bacterial abundances. An alternative explanation is that since polar membrane lipids were similar inside and outside the slick, the abundance data are indicating that there was more biomass per cell inside the slick than outside the slick (i.e.…”
Section: Microbial Biomass and Abundancesupporting
confidence: 85%
“…Indeed, a study that traced the carbon isotopic signatures of the planktonic food web in the Gulf of Mexico after the Deepwater Horizon spill concluded that there was trophic transfer of carbon from oil to bacteria to higher levels in the food web (Graham et al 2010). In addition, previous research on the response of the microbial community to the Prestige oil spill off the coast of Spain suggests that grazing control resulted in an increase in bacterial production and respiration within oil contaminated waters without a subsequent increase in bacterial biomass (Bode et al 2006). However, it must be noted that these two studies were conducted in nearshore environments that were unlikely to have been as nutrient depleted as waters we studied in proximity to the Deepwater Horizon site.…”
Section: Grazing Control Of Microbial Standing Stocks Within Slicksmentioning
confidence: 99%
“…After fuel addition bacterial abundances usually tend to increase according to both experimental and field observations (Ohwada et al ., 2003; Nayar et al ., 2005; Sargian et al ., 2005; Bode et al ., 2006). Our results also show an overall increase of PA after PAHs treatment as compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of oil spills on the natural bacterioplankton communities of coastal ecosystems have been studied using in situ measurements (e.g. Bode et al 2006), laboratory experiments (Maruyama et al 2003, Castle et al 2006, Cappello et al 2007a) and experimental systems such as mesocosms , Ohwada et al 2003, Cappello et al 2007b). This last type of approach avoids the effects caused by advection, diffusion and mixing under natural conditions, and it also offers the possibility of comparison with natural populations to which PAHs have not been added, thus allowing statistical testing of hypotheses.…”
Section: Introductionmentioning
confidence: 99%